Historical and legal aspects of the formation and development of electoral legal relations in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article is devoted to topical issues of the evolution of the electoral law and electoral legal relations in the history of the Republic of Kazakhstan. The aim of the work is to study the main stages of formation and development of electoral legal relations in the territory of Kazakhstan. In particular, the evolution of the institutions of electoral law in the development of the political system of the Kazakh Khanate, the specificity of electoral legal relations after accession to Russia and the Soviet period are analyzed. The urgency of the problem is determined by the socio-political significance for the Kazakhstani state and the society of the institution of elections as an unconditional component of their democratic development. When writing the article, both general scientific and private scientific methods of research (dialectical, historical, comparative legal, special-legal, logical) were used. The practical significance of the article lies in the possibility of using the results obtained in improving the existing electoral legislation of the Republic of Kazakhstan, as well as in law enforcement practice in the sphere of elections of various levels.Key words: Elections, electoral process, vote, electoral laws, election campaign, electoral rights, principles.